A chinese medicine formula (kunbixiao granule) for female rheumatoid arthritis: Study protocol for a double-blind, randomized, placebo-controlled trial - Wan, Yingying; Yang, Jiaxi; Ma, Tianyue; Wang, Wenqian; Wang, Haonan; Sun, Wenting; Ye, Wanting; Yang, Lin; Kou, Qiuai (Frontiers in Pharmacology, 2022)
Introduction: Rheumatoid arthritis (RA) is a chronic autoimmune disease affecting female more than male. Clinical symptoms, disease activity and comorbidities are more severe in female. Moreover, the choice of treatment of female is limited during childbearing age due to the side effects of current drugs. Therefore, developing novel and safer drugs for female is urgently needed. Kunbixiao granules (KBXG), a traditional Chinese medicine (TCM) formula, has been applied to treat female RA patients in our centre as a complementary therapy. However, there is insufficient evidence for it effect. Therefore, we aim to conduct a randomized, controlled, double-blind clinical trial to confirm the efficacy and safety of KBXG for the treatment of female RA. Methods: This study is a single-center, double-blind, randomized, parallel group, placebo-controlled clinical trial. A total of 90 female RA patients with a Disease Activity Score for 28 joints (DAS28) > 3.2 will be enrolled. They will be randomly assigned to receive either KBXG or placebo for 12 weeks with four scheduled visits. The change in DAS28 will be examined as the primary outcomes. The secondary outcomes include rate of achieving 20%, 50%, 70% improvement in the American College Rheumatology criteria (ACR20, ACR50, ACR70), TCM syndrome score, visual analogue scale (VAS), average hands grip strength, health assessment questionnaire disability index (HAQ-DI), 7-joint ultrasound score (US7), and self-rating anxiety scale (SAS). Any possible adverse events will also be recorded. Discussion: This trial will provide evidence of KBXG in reducing disease activity, improving clinical symptoms and quality of life of female RA patients. However, the long-term effects of KBXG on female RA patients still needs a further follow-up.